Genetics of Cushing's disease. (21st May 2022) - Simon, Julia; Theodoropoulou, Marily
Abstract: Corticotroph tumours are primarily sporadic monoclonal neoplasms and only rarely found in genetic syndromes. Recurrent mutations in the ubiquitin specific protease 8 (USP8) gene are found in around half of cases. Mutations in other genes such as USP48 and NR3C1 are less frequent, found in less than 20% of cases. TP53 and ATXR mutations are reported in up to one out of four cases, when focusing in USP8 wild type or aggressive corticotroph tumours and carcinomas. At present, USP8 mutations are the primary driver alterations in sporadic corticotroph tumours, TP53 and ATXR mutations may indicate transition to more aggressive tumour phenotype. Next generation sequencing efforts have identified additional genomic alterations, whose role and importance in corticotroph tumorigenesis remains to be elucidated.